(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
Callinectes sapidus Rathbun, 1896, is artisanal caught in the coastal lagoon system from Uruguay to Brazil. To analyze their reproductive strategy, 422 individuals were extracted from Laguna de Rocha (34°33’S, 54°22’W), which were sexed, measured and dissected. The mean size (CWm) differed significantly between the seasons (H= 66,37; p<<0,05). The largest crabs occurred in winter, decreasing in size towards spring. The sex ratio (M:F) differed significantly from 1:1 and showed significant variability between seasons (F3,372=1658,37; p<<0,01). Four categories of ovarian development were identified: immature, pre-vitellogenic, mature and in reabsorption. Mean size of females with immature and mature ovaries differed significantly (H= 41,17; p<0,05). No significant differences were found between CWm of ovigerous females with eggs in different stages of development (F2,60=0,088; p=0,91). The sizes at first maturity (L50%) physiological and morphological did not show significant differences within sex (females: K-S: D=0,06, p=0,76; males: K-S: D=0,04, p= 0,99). However, they were significantly different between sexes (morphological K-S: D=0,62, p<<0,05 and gonadal K-S: D=0,64, p<<0,05). Due to its importance at the regional and local level, as a fishing and ecosystem resource, it is suggested to intensify studies of the population of this crustacean.